Restorative Approaches to Managing Children in Conflict with the Law - Anwar, Iryana; Prihatmini, Sapti; Azizah, Ainul; Suarda, I Gede Widhiana (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2024)
This study investigates the regulation of action sanctions through a restorative approach for children in conflict with the law (ABH) within the juvenile criminal justice system in Indonesia. The objective is to analyze the alignment of these regulations with the principles of child protection and restorative justice. Utilizing a normative juridical method that incorporates statutory and conceptual approaches, the findings indicate that Article 82 of the Juvenile Criminal Justice System Law (SPPA Law) embodies a restorative justice approach, striving to balance community protection with the rehabilitation of ABH. However, the implementation is suboptimal, and many ABH continue to receive prison sentences. This suggests that the principles of the best interests of the child, the right to development, and respect for children’s views have not been adequately upheld. There is a need for further refinement of action sanctions to better align with restorative justice and address the needs of ABH.